A practical and economical strategy to mitigate salinity stress through seed priming - Khan, Muhammad Owais; Irfan, Muhammad; Muhammad, Asim; Ullah, Izhar; Nawaz, Sultan; Khalil, Mussaddiq Khan; Ahmad, Manzoor (Frontiers in Environmental Science, 2022)
Soil salinity is highly dominant in semi-arid and arid areas, and it is one of the major abiotic problems of greater than 30% of irrigated land in the globe. The concentrations of various salts such as NaCl, MgSO4, KCl, MgCl2, CaSO4, Na2SO4 and Na2CO3 cause saline stress; however, NaCl is the most abundant salt in the soil. Soil salinity negatively affected various growth stages of crops at a different rate, but seed germination and seedling growth are the two most sensitive growth periods to soil salinity. Further, salinity could affect seed germination due to osmotic potential or due to specific toxic ion effects, and it decreases germination percentage and increases germination time, and high salt stress is responsible for delaying seed germination. Therefore, it is necessary to alleviate the negative impact of soil salinity during seedling growth periods, so the growth of crops in salt-affected soil will be much more enhanced. Seed priming is the utmost effective technique that could mitigate the harmful impact of soil salinity. This methodology minimizes the salinity tolerance; moreover, it strengthens the defense system of crops. In this technique, hydration level within the seeds is controlled by applying pre-sowing treatments, allowing specific pre-germinative metabolic processes to occur and prevent radical emergence. Besides, seed priming decreases the seed germination time and improves antioxidative enzymes activity, stopping or minimizing reactive oxygen species' adverse effects. It enhances the seedling performance with rapid and homogenous germination, vigorous and dynamic growth of the seedling, achieving a physiological situation leading to quick and enhanced emergence and germination of various crops. This review covers the mechanisms of seed priming, which induce biochemical, physiological, and morphological mechanisms in saline stress. More studies needed to be conducted on different crops at molecular and metabolic levels, which will further elaborate crop's tolerance through the seed priming process.